The Profitability of Nigerian Banks - NWUDE, E Chuke (Asian Journal of Empirical Research, 2013)
The paper investigates the extent to which stocks of commercial banks listed on Nigeria Stock Exchange (NSE) are positioned on the selected profitability performance indices over the period 2000-2010. The profitability performance was determined using return on assets, return on equity, earnings per share, dividend per share, earnings yields, dividend yields and increments in net asset per share. The findings revealed that First Bank of Nigeria was truly the first in terms of yield on earning assets, earnings per share, dividend per share, net asset per share, and the most priced bank in Nigeria. Diamond was the most profitable bank in terms of earnings yield and dividend yield while StanbicIbtc and Wema were the most profitable banks in terms of return on assets and return on equity respectively for the study period.